Penerapan Metode Rational Unified Process pada Aplikasi Monitoring Periodic Service Alat Berat - Putri Kusuma Wardani (Universitas Sebelas Maret, 2017)
Product Support is one of the divisions in the company who deliver technical support to customers, especially in terms of after sales service. Commonly, the data obtained by the product support division at PT Hexindo Adiperkasa Tbk is still a general information concerning the units owned by the company. This data needs to be analyzed and then reprocessed using an application such as Excel spreadsheets to find out the periodic service of heavy machinery in each period, in order that the data processing time is relatively longer and allow for errors or human error. In addition, the data processing tends to be ineffective.This research aims to design a